No extension without representation? Evidence from a natural experiment in collective bargaining - Alexander Hijzen; Pedro S. Martins (IZA Journal of Labor Economics, 2020)
In many countries, collective bargaining coverage is enhanced by government-issued extensions that widen the reach of collective agreements beyond their signatory parties to all firms and workers in the sector. This paper analyzes the causal impact of extensions using a natural experiment in Portugal that resulted in a sharp and unanticipated decline in the extension probability of agreements. Our results, based on a regression discontinuity design, indicate that extensions had a negative impact on employment growth. This effect is concentrated among nonaffiliated firms, which may reflect the limited representativeness of employer associations.
Keywords: J52; J58; J21; 330; industrial relations; employer associations; wage setting; employment